Diets that differ in their FODMAP content alter the colonic luminal microenvironment - Halmos, E.; Christophersen, Claus; Bird, A.; Shepherd, S.; Gibson, P.; Muir, J. (B M J Group, 2015)
Objective: A low FODMAP (Fermentable Oligosaccharides, Disaccharides, Monosaccharides And Polyols) diet reduces symptoms of IBS, but reduction of potential prebiotic and fermentative effects might adversely affect the colonic microenvironment. The effects of a low FODMAP diet with a typical Australian diet on biomarkers of colonic health were compared in a single-blinded, randomised, cross-over trial.Design: Twenty-seven IBS and six healthy subjects were randomly allocated one of two 21-day provided diets, differing only in FODMAP content (mean (95% CI) low 3.05 (1.86 to 4.25) g/day vs Australian 23.7 (16.9 to 30.6) g/day), and then crossed over to the other diet with =21-day washout period. Faeces passed over a 5-day run-in on their habitual diet and from day 17 to day 21 of the interventional diets were pooled, and pH, short-chain fatty acid concentrations and bacterial abundance and diversity were assessed.Results: Faecal indices were similar in IBS and healthy subjects during habitual diets. The low FODMAP diet was associated with higher faecal pH (7.37 (7.23 to 7.51) vs 7.16 (7.02 to 7.30); p=0.001), similar short-chain fatty acid concentrations, greater microbial diversity and reduced total bacterial abundance (9.63 (9.53 to 9.73) vs 9.83 (9.72 to 9.93) log10 copies/g; p<0.001) compared with the Australian diet. To indicate direction of change, in comparison with the habitual diet the low FODMAP diet reduced total bacterial abundance and the typical Australian diet increased relative abundance for butyrate-producing Clostridium cluster XIVa (median ratio 6.62; p<0.001) and mucus-associated Akkermansia muciniphila (19.3; p<0.001), and reduced Ruminococcus torques.Conclusions: Diets differing in FODMAP content have marked effects on gut microbiota composition. The implications of long-term reduction of intake of FODMAPs require elucidation.